Video and audio platforms for improving listening skills in Spanish´s students of EFL: A preliminary and descriptive study (ELT Forum: Journal of English Language Teaching, 2022)
Learning English as a foreign language can be challenging because it requires the development of tools which allows an effective communication process. In this sense, the phonetic differences between Spanish and English are one of the reasons why it is difficult to develop listening skills for Spanish native speakers. Thus, in this research, a didactic strategy based on common audio and video platforms was designed in order to improve this ability in a sample of students. The sample was selected at convenience and consisted of fifteen students from an English intermediate course. The strategy was divided into three parts: a diagnostic test to demonstrate the level of listening; learning activities; and an exit test. A descriptive study was conducted. The obtained results showed students’ progressive improvement in pragmatics, understanding, and intonation. In addition, the results indicated that the use of alternative methods, mediated by new technologies, seems to be equal or more effective than traditional teaching and a better learning of English is perceived by using remote strategies than in face-to-face ones.